(untitled) (Economics and region, 2023)
The purpose of the article is to improve the models for assessing the cost of capital as an investment resource and a factor of production, as well as the tools for optimizing the capital structure of a business. War requires significant resources, including financial ones. In addition to credit injections by international institutions, it is extremely important that Ukraine’s needs for these resources are met by Ukrainian business.After all, under martial law, business plays an important role in maintaining the vital functions of the national economy, which is being bled dry every day by the war with Russia and sometimes by the economic and political selfishness of neighboring countries that block economic decisions important for Ukraine. Surviving in a war, ensuring that businesses are profitable and paying taxes on a regular basis is not an easy task. The author argues that the success of business in any field of activity in the difficult conditions of martial law depends on the professionalism of financial managers. The author proposes improved models for determining the cost of capital involved in the economic processes of business as an investment resource and a factor of production, and tools for optimizing the capital structure of an enterprise, which are considered in a logical sequence and in conjunction with the weighted average cost of capital model. Since the professional portfolio of financial managers should include not only the considered models of capital management, but also other financial instruments, this will be the focus of further research.